Horizontal ecological compensation and urban inclusive green growth: evidence from China - Wang, Hengli; Li, Weiyi; Xiao, Hongce; Wang, Daoli (Frontiers in Public Health, 2024)
Horizontal ecological compensation (HEC) has the potential to incentivize inclusive green growth in cities. Using the multi-stage difference-in-differences (DID) method, this study examines the impact of HEC policies as a quasi-natural experiment. Panel data are analyzed; the data pertain to 87 cities in the Yangtze River Basin, from 2007 to 2020. The findings indicate that HEC policies significantly contribute to inclusive green growth, with consistent effects across different estimators. The moderating effect test reveals that urban industrial pollution levels and green innovation are key pathways through which HEC policies influence inclusive green growth. Further analysis shows that the positive impact of HEC is more pronounced in watersheds with high marketization and in downstream regions, suggesting that HEC may exacerbate regional disparities in inclusive green growth. This study offers insights for China and also for other developing countries seeking to promote urban inclusive green growth and achieve sustainable development goals.